Kematangan Emosional, Percaya Diri dan Kecemasan Pegawai Menghadapi Masa Pensiun - Sutrisno, Edy (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. This study aimed to determine the relationships between emotional maturity, self-confidence and the anxiety to face retirees. Subjects were 60 civil servants who are resident residing in the Territory Housing Complex Tandes. Data retrieval tool used is the scale emotional maturity, self-confidence scale and face the anxiety scale pension. Data were analyzed by using multiple reggression. The results showed: first, there was a negative relationship between emotional maturity and anxiety civil servants. It showed when one's emotional maturity is high, then the anxiety state employees retirement will decrease. Second, showed that there was a negative relationships between self-confidence and anxiety civil servants. when self-confidence is high, then the anxiety state employees retire-ment will decrease.Key Words: emotional maturity, self-confidence and employee’s anxiety in fa-cing the future pension.